Electrochemical removal of mercury from contaminated aqueous solutions - Feldt, Emma (My University, 2019)
Because mercury is one of the most toxic heavy metals known, there are multiple techniques for the removal of mercury from aqueous solutions. A new technique introduced uses electrochemical alloy formation to reduce mercury concentrations. By controlling the potential applied, this method has been proven to reduce mercury in aqueous solutions from different initial concentrations. The main conclusion is that the method can reduce the amount of mercury in solution to under 6 µg/L, which is the World Health Organisation’s guideline value for drinking water.
Keywords: Fysik; Physical Sciences